Infinite-dimensional VARs and factor models - Alexander Chudik; Hashem Pesaran (European Central Bank (ECB), 2009)
This paper introduces a novel approach for dealing with the 'curse of dimensionality' in the case of large linear dynamic systems. Restrictions on the coefficients of an unrestricted VAR are proposed that are binding only in a limit as the number of endogenous variables tends to infinity. It is shown that under such restrictions, an infinite-dimensional VAR (or IVAR) can be arbitrarily well characterized by a large number of finite-dimensional models in the spirit of the global VAR model proposed in Pesaran et al. (JBES, 2004). The paper also considers IVAR models with dominant individual units and shows that this will lead to a dynamic factor model with the dominant unit acting as the factor. The problems of estimation and inference in a stationary IVAR with unknown number of unobserved common factors are also investigated. A cross section augmented least squares estimator is proposed and its asymptotic distribution is derived. Satisfactory small sample properties are documented by Monte Carlo experiments.
Keywords: C10; C33; C51; 330; Large N and T Panels; Factor models; Global VAR; VAR; Weak and Strong Cross Section Dependence; VAR-Modell; Faktorenanalyse; Monte-Carlo-Simulation; Investition; Wirtschaftswachstum; Theorie; Schätzung; Welt